1996
DOI: 10.1007/bf00057587
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a regulatory protein complex on RNA polymerase III promoter of human retroposons of Alu family

Abstract: Abundant human retroposons of the Alu family produce few RNA polymerase III (RPIII)-dependent transcripts in vivo. This suggests that either the bulk of the repeats has no proper promoter elements or that transcription of Alu by RPIII is repressed. In this study, we analyzed complexes formed by human nuclear proteins with the Alu B-box and with an adjacent downstream sequence (DB-sequence). Four complexes (C1-C4) were detected and two of them (C2 and C3) were found to be induced by different proteins. C3 forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In our previous work, evidence was presented for the assembly of specific protein complexes on an Alu sub‐sequence located within and just downstream of its promoter B‐box [34–36]. In this study we show that one of the complexes is down‐regulated in adenovirus‐5‐infected cells, which is consistent with the view that it may be a Pol‐III‐repressor complex.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…In our previous work, evidence was presented for the assembly of specific protein complexes on an Alu sub‐sequence located within and just downstream of its promoter B‐box [34–36]. In this study we show that one of the complexes is down‐regulated in adenovirus‐5‐infected cells, which is consistent with the view that it may be a Pol‐III‐repressor complex.…”
supporting
confidence: 90%
“…Deletion mapping of the internal promoter elements essential for the Pol‐III‐dependent Alu transcription in vitro [13,14] indicated that one of the elements (directing element) is located in the Alu subregion between nt 63 and 140 covering the promoter B‐box. This subregion was also found to interact in vitro with HeLa nuclear proteins [34,35,41]; one of which may be basal transcription factor TFIIIC which preferentially binds to the B‐box region [3,8]. Figure 1 shows part of the corresponding Alu subregion and oligonucleotide probes used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter finding is reminiscent of the localization of other insulator proteins that were proposed to establish chromatin loops to define independent domains of transcriptional activity [160]. In mammals, about 500 000 copies of Alu repeats, which account for 5% of the genome content, contain B-box sequences [165]. This large fraction of potential TFIIIC-binding sites indicates a potential role for at least a fraction of Alu elements in the spatial organization of the mammalian genome.…”
Section: Epigenetic Regulation and Chromosomal 3d Interactionsmentioning
confidence: 96%